Search for the flavor-changing neutral current decay B0s--> mu(+) mu(-) in pp Collisions at sqrt[s] = 1.96 TeV with the D0 detector. - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Agelou, M; Agram, J; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; et al. (2005)
We present the results of a search for the flavor-changing neutral current decay B(0)(s)--> mu(+) mu(-) using a data set with integrated luminosity of 240 pb(-1) of pp collisions at sqrt[s] = 1.96 TeV collected with the D0 detector in run II of the Fermilab Tevatron collider. We find the upper limit on the branching fraction to be B(B(0)(s)--> mu(+) mu(-)) < or= 5.0 x 10(-7) at the 95% C.L. assuming no contributions from the decay B(0)(d)--> mu(+) mu(-) in the signal region. This limit is the most stringent upper bound on the branching fraction B(0)(s)--> mu(+) mu(-) to date.